Kepentingan Australia dalam Diplomasi Pembangunan terhadap Nauru - Riady Ibnu Khaldun; Erwin Amiruddin; Asma Amin (Department of International Relations, Hasanuddin University, 2023)
This research examines Australia's interests in Nauru in development diplomacy and the obstacles to achieving or achieving these interests. The concept used in analyzing this phenomenon is the concept of Development Diplomacy and National Interests. Furthermore, in this study using qualitative research methods with data collection techniques carried out by literature studies or Internet research where all data comes from secondary data. The results of this study indicate that Australia's interest in Nauru in conducting development diplomacy is to maintain its position in the Pacific Region, namely to ensure regional security. Preventing Chinese influence in the Pacific through harmonious relations with the creation of a political partnership between Australia and Nauru. Maintaining the stability of the Pacific Region, one of which makes Nauru a location for Australian Illegal Immigration. And strengthening bilateral relations between the two parties so that Australia can control Nauru's natural resources as well as encourage the implementation of development cooperation. In addition, obstacles to achieving Australia's interests in Nauru are threats to Australia's position in the Pacific region, China's influence which threatens Australia, challenges for Australia in maintaining stability in the Pacific region and challenges for Australia to bilateral relations with Nauru. Penelitian ini mengkaji mengenai kepentingan Australia terhaap Nauru dalam diplomasi pembangunan dan hambatan dalam mencapai atau meraih kepentingan tersebut. Konsep yang digunakan dalam menganalisis fenomena ini adalah konsep Diplomasi Pembangunan dan Kepentingan nasional. Selanjutnya, pada penelitian ini mengunakan metode penelitian kualitatif dengan Teknik pengumpulan data dilakukan dengan studi literatur atau Internet research di mana keseluruhan data berasal dari data sekunder. Hasil penelitian ini menunjukkan bahwa kepentingan Australia terhadap Nauru dalam melakukan diplomasi pembangunan adalah mempertahankan posisinya di Kawasan Pasifik yakni untuk menjamin terciptanya keamanan regional. Mencegah pengaruh China di Pasifik melalui hubungan harmonis dengan terciptanya kemitraan politik antara Australia dengan Nauru. Menjaga stabilitas Kawasan Pasifik satu di antaranya menjadikan Nauru sebagai lokasi penampungan Imigrasi Ilegal Australia. Dan memperkuat hubungan bilateral di antara kedua belah pihak agar Australia bisa menguasai sumber daya alam Nauru termasuk juga mendorong terlaksanannya kerjasama pembangunan. Selain itu hambatan dalam mencapai kepentingan Australia terhadap Nauru adalah Ancaman terhadap posisi Australia di Kawasan Pasifik, Pengaruh China yang Mengancam Australia, Tantangan bagi Australia dalam menjaga stabilitas di Kawasan Pasifik dan Tantangan bagi Australia terhadap hubungan bilateral dengan Nauru.